Perspective Criticism and Preaching: Merging Character and Congregation (Homiletic, 2017)
This article suggests one possible way that perspective criticism, an emerging methodology within biblical studies, can inform homiletics. Perspective criticism provides the homiletician with an understanding of why it is that listeners might either condone or condemn a character in the sermon. This being the case, the preacher can use the planes to either have the congregation merge with a particular character or be distanced from a particular character.